RESPONSE OF CERTAIN PHYTOCHEMICAL CONSTITUENTS IN SWEET PEPPER LEAVES TO SOME BIO-STIMULANTS UNDER TWO TYPES OF SALINITY - A.A, Arafa; M.A, Khafagy; A.M, Abo-El Kheer; El-Banna, M.F (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
High salinity level of NaCl and CaCl2 (4000 mg/L) markedly increased whereas the low levels and its combination decreased electrolyte leakage percentage (E.L. %) in sweet pepper leaves as compared to the unstressed plants. In addition, application of all selected bio-regulators used at both applied levels, in most cases, alleviated the harmful effect of salinity on E.L. % especially ascorbic acid at 50 mg/L. Relative water content (RWC) and photosynthetic pigments were significantly increased thereafter decreased as salinity levels increased. In addition, CaCl2 at low level caused a great increase in RWC % followed by NaCl+CaCl2 and NaCl (2000 mg/L). While, pre-soaking seeds in both levels of the applied bio-stimulants caused a significant increase in RWC % and the photosynthetic pigments concentrations . In addition, AsA at 50 mg/L or SA at 75 mg/L was more effective in this respect as compared to the untreated plants. Ascorbic acid, proline, total phenols as well as total soluble carbohydrates concentrations in sweet pepper shoot were increased with increasing salinity levels from 2000 to 4000 mg/L of all salinity types. In addition, NaCl led to a great increase followed by NaCl+CaCl2 and CaCl2 as compared to the unstressed plants. In addition, pre-soaking seeds in SA, AsA, tocopherol and yeast extract at both levels increased ascorbic acid, proline, total phenols as well as total soluble carbohydrates concentrations under saline conditions. Moreover, AsA at 50 mg/L or SA at 75 mg/L was more effective in this respect as compared with the other treatments